2016
DOI: 10.1007/s00704-016-1856-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of snow cover changes on surface radiation and heat balance based on the WRF model

Abstract: The snow cover extent in mid-high latitude areas of the Northern Hemisphere has significantly declined corresponding to the global warming, especially since the 1970s. Snow-climate feedbacks play a critical role in regulating the global radiation balance and influencing surface heat flux exchange. However, the degree to which snow cover changes affect the radiation budget and energy balance on a regional scale and the difference between snow-climate and land use/ cover change (LUCC)-climate feedbacks have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Figure 13 presents the spatial pattern of the mean diurnal peak value and peak time of surface energy fluxes from June to September in 2008 for the headwater and its surrounding area. Comparing Figure 13 to Figure 1b, the peak value of Rn in high mountain peaks is relatively lower than it in the valley and the flat area, because of increased snow cover at higher elevation (Minder et al, 2016; Yu et al, 2017). The diurnal peak time of Rn shows slight spatial variations according to the terrain height, close to local noontime.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 13 presents the spatial pattern of the mean diurnal peak value and peak time of surface energy fluxes from June to September in 2008 for the headwater and its surrounding area. Comparing Figure 13 to Figure 1b, the peak value of Rn in high mountain peaks is relatively lower than it in the valley and the flat area, because of increased snow cover at higher elevation (Minder et al, 2016; Yu et al, 2017). The diurnal peak time of Rn shows slight spatial variations according to the terrain height, close to local noontime.…”
Section: Resultsmentioning
confidence: 97%
“…The regional statistic results showed that both rain-fed farmland and paddy fields had a similar change tendency for albedo and ET during the growing season. Generally, the albedo of water was lower than that of other land use types [59], and as a result, the albedo of paddy fields was much lower than that of rain-fed farmland in May and June when the paddy fields were filled with water. Significant albedo differences were detected in May and June (spring), −0.035 ± 0.031 and −0.028 ± 0.027, respectively.…”
Section: Comparison Of Key Biogeophysical Parameters In Rain-fed Farmmentioning
confidence: 90%
“…LUC-induced changes of surface biogeophysical characteristics, such as albedo 14 , surface roughness 15 , and Bowen ratios 16,17 , have direct impacts on the heterogeneity and quantity of local temperature, humidity and wind speed, which make biogeophysical processes critical to the local climate system 4,18 . At present, worldwide land cover changes have received extensive attention due to their significant effects on large-scale climate, including changes in deforestation and afforestation 1922 , desertification 23 , and snow and ice cover 24 . Meanwhile, meso-micro-scale climate changes resulting from typical LUC are similarly notable and may even be stronger than background climate change 10,2527 .…”
Section: Introductionmentioning
confidence: 99%